Differences in the course of rehabilitation and outcomes for publicly insured pediatric patients after anterior cruciate ligament reconstruction. (November 2022) - Greenberg, Elliot; Butler, Lauren; Giampetruzzi, Nicholas; Link, Meredith; Prati, Victor; Weaver, Adam; Saper, Michael
Abstract: Objective: Examine the effect of insurance type on physical therapy (PT) utilization and outcomes within pediatric and adolescent patients after anterior cruciate ligament reconstruction. Design: Multicenter retrospective cohort study. Methods: PT visits and functional hop test performance were extracted into a shared database. The average number of PT visits per week was assessed overall and by time period. Independent samples t -test examined the effect of insurance on PT utilization and the effect of insurance status on the odds of passing single-legged hop tests was assessed using multivariable logistic regression. Results: A total of 281 patients (15.7 ± 1.9, 42% female) were included in this analysis. Of these, 128 (45%) had public insurance. Publicly insured patients experienced a longer delay from surgery to hop test (8.3vs7.7 months, p = 0.009), attended overall fewer PT visits per week (0.92vs1.04, p = 0.005), with most of the decreased frequency occurring between weeks 7–24. Insurance status had a significant effect on the odds of passing the single leg hop test (2.72; 95%CI, 1.27–5.81). Conclusion: Publicly insured patients average a lower number of weekly PT visits, experienced a longer delay from surgery to hop testing and were 2.7 times less likely to pass the single leg hop for distance test. Highlights: Publicly insured patients experience different patterns of rehabilitation. After ACLR publicly insured youth attended fewer weekly PT sessions. After ACLR publicly insured youth athletes were less likely to pass functional tests.